Regulatory Overview of Biosimilars: Current Scenario and Future Opportunities - S. Grewal, Ajmer; Lather, Viney; Bhardwaj, Shashikant; Pandita, Deepti (Applied Clinical Research, Clinical Trials and Regulatory Affairs, 2015)
Background: Biosimilar products (biosimilars) are highly similar versions of approved and authorized biological medicines (which are used to treat a wide range of diseases including cancer, rheumatoid arthritis, diabetes and anemia) that have come as revolutionary paradigm in therapeutics. They are similar copies of already approved biologicals (reference products), produced by more reliable methods. Biosimilars are able to reduce the cost of the reference product by 20% to 35%. Objectives: This mini-review article has been planned to discuss the regulatory aspects of the biosimilars as well as basic facts about the biosimilars. Recent developments in the area of biosimilars will be discussed along with future opportunities and challenges in the field of manufacturing and marketing of the biosimilars in biopharmaceutical industry. Discussion: The main driving force behind the development of biosimilars is the expiry of patents for the approved biological products worldwide. The patent protection for the approved biological products have either expired or about to expire. Thus the market is opening for ‘biosimilars’. The global market for biosimilars is expected to reach USD 6.22 billion by 2020 from USD 2.29 billion in 2015. The regulatory requirements for the approval of biosimilars are not as easy as that of the conventional generic drugs. Europe, United States, China, India, Japan, Canada & World Health Organization have published guidelines for biosimilars but there is no harmonised pathway for regulation of biosimilars.
Keywords: current scenario